Barbie - od przedmiotu do rzeczy - Woźniak-Czech, Ewelina (Przestrzenie Teorii, 2023)
Barbie, the doll-symbol, the pop culture icon and significant prop on the artistic, political, social and business scenes, has been arousing emotions in subsequent generations for several decades. It is worth noting, however, that today Barbie is no longer just a passive instrument illustrating desired ideas, but has become a factor creating reality independent of her creators. In the present discussion, the author focuses on the interpretation of the phenomenon of Barbie perceived as an object and a thing in the sense of the Italian philosopher Remo Bodei. The article attempts to trace the transformation of the image of the Barbie doll from its creation to modern times, when its popularity peaked thanks to the excellent marketing strategy accompanying the distribution of Greta Gerwing’s 2023 film Barbie.